Seropositivity and risk factors associated with Toxoplasma gondii infection in wild birds from Spain. - Oscar Cabezón; Ignacio García-Bocanegra; Rafael Molina-López; Ignasi Marco; Juan M Blanco; Ursula Höfle; Antoni Margalida; Antoni Margalida; Esther Bach-Raich; Laila Darwich; Israel Echeverría; Elena Obón; et al. (PLoS ONE, 2011)
Toxoplasma gondii is a zoonotic intracellular protozoan parasite of worldwide distribution that infects many species of warm-blooded animals, including birds. To date, there is scant information about the seropositivity of T. gondii and the risk factors associated with T. gondii infection in wild bird populations. In the present study, T. gondii infection was evaluated on sera obtained from 1079 wild birds belonging to 56 species (including Falconiformes (n=610), Strigiformes (n=260), Ciconiiformes (n=156), Gruiformes (n=21), and other orders (n=32), from different areas of Spain. Antibodies to T. gondii (modified agglutination test, MAT titer ≥1:25) were found in 282 (26.1%, IC(95%:)23.5-28.7) of the 1079 birds. This study constitute the first extensive survey in wild birds species in Spain and reports for the first time T. gondii antibodies in the griffon vulture (Gyps fulvus), short-toed snake-eagle (Circaetus gallicus), Bonelli's eagle (Aquila fasciata), golden eagle (Aquila chrysaetos), bearded vulture (Gypaetus barbatus), osprey (Pandion haliaetus), Montagu's harrier (Circus pygargus), Western marsh-harrier (Circus aeruginosus), peregrine falcon (Falco peregrinus), long-eared owl (Asio otus), common scops owl (Otus scops), Eurasian spoonbill (Platalea leucorodia), white stork (Ciconia ciconia), grey heron (Ardea cinerea), common moorhen (Gallinula chloropus); in the International Union for Conservation of Nature (IUCN) "vulnerable" Spanish imperial eagle (Aquila adalberti), lesser kestrel (Falco naumanni) and great bustard (Otis tarda); and in the IUCN "near threatened" red kite (Milvus milvus). The highest seropositivity by species was observed in the Eurasian eagle owl (Bubo bubo) (68.1%, 98 of 144). The main risk factors associated with T. gondii seropositivity in wild birds were age and diet, with the highest exposure in older animals and in carnivorous wild birds. The results showed that T. gondii infection is widespread and can be at a high level in many wild birds in Spain, most likely related to their feeding behaviour.